2018
DOI: 10.7566/jpsj.87.041004
|View full text |Cite
|
Sign up to set email alerts
|

Towards ab initio Calculations with the Dynamical Vertex Approximation

Abstract: While key effects of the many-body problem-such as Kondo and Mott physics-can be understood in terms of onsite correlations, non-local fluctuations of charge, spin, and pairing amplitudes are at the heart of the most fascinating and unresolved phenomena in condensed matter physics. Here, we review recent progress in diagrammatic extensions to dynamical mean-field theory for ab initio materials calculations. We first recapitulate the quantum field theoretical background behind the two-particle vertex. Next we d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 138 publications
(200 reference statements)
0
48
0
Order By: Relevance
“…Regarding the impurity solver, we used hybridization expansion algorithm of the continuous-time quantum Monte Carlo (CTQMC) method 26,27 in the region U/W 1.5. In the strong-coupling regime U/W 1.0, we used the Hubbard-I approximation to obtain a stable solution, avoiding statistical errors (see Appendix A for some remarks).…”
Section: B Exemplary Results and Aim Of This Papermentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding the impurity solver, we used hybridization expansion algorithm of the continuous-time quantum Monte Carlo (CTQMC) method 26,27 in the region U/W 1.5. In the strong-coupling regime U/W 1.0, we used the Hubbard-I approximation to obtain a stable solution, avoiding statistical errors (see Appendix A for some remarks).…”
Section: B Exemplary Results and Aim Of This Papermentioning
confidence: 99%
“…The basic idea is presented in Ref. 3, which showed that the antiferromagnetic (AFM) transition temperature covers the paramagnetic Mott transition in the Hubbard model. For early and recent reviews of the method, see Refs.…”
Section: A Susceptibility In the Dmftmentioning
confidence: 99%
See 3 more Smart Citations